Hall, Wiececk, & Finkelman, American Legal History - Case And Materials - Scott, John (Teaching History: A Journal of Methods, 1992)
This book brings together approximately 200 documents covering the span of American history from 1620 to the 1980s. Much of this material is heavily excerpted. Types of documents presented include colonial and state constitutions and laws, Federalists and anti-Federalist papers, political platforms and speeches, Supreme Court decisions and dissents, presidential veto messages, parts of legal treatises (Cesare Beccaria, John Cobb, Thomas M. Cooley, Christopher G. Tiedemann. 0. W. Holmes), Black Codes, and more.